Early Summer Dissolved Oxygen Characteristics in Restored Streams in Seoul - (:unkn) unknown (My University, 2013)
Abstract : This paper presents an evaluation of stream restoration projects in Seoul with a focus on dissolved oxygen. Five test sites across four streams were measured for dissolved oxygen (DO) in late May to early June in 2012 and compared against a set of minimum and maximum thresholds. Only one test site, Hwarang-cheon, showed measurements below 6 mg/l DO. Towards the upper limit, the Hwarangcheon site was the only tested stream which was not at risk of DO supersaturation. The Danghyeon-cheon site had the highest probability of supersaturation, with DO saturation exceeding 130% expected 86.5% of the time. When measured every hour during daytime, DO levels showed diurnal variations, peaking in the afternoon. However, they showed inconsistent results along transects of the streams. Overall, the streams are rich in DO. To maintain the streams in good standing, nutrient loading should be addressed to prevent potential algal bloom induced hypoxic events down the line.
Keywords: Water Quality; Dissolved Oxygen; Stream Restoration; Runoff